If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -7(x + -3) = 2x + -10 Reorder the terms: 9 + -7(-3 + x) = 2x + -10 9 + (-3 * -7 + x * -7) = 2x + -10 9 + (21 + -7x) = 2x + -10 Combine like terms: 9 + 21 = 30 30 + -7x = 2x + -10 Reorder the terms: 30 + -7x = -10 + 2x Solving 30 + -7x = -10 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 30 + -7x + -2x = -10 + 2x + -2x Combine like terms: -7x + -2x = -9x 30 + -9x = -10 + 2x + -2x Combine like terms: 2x + -2x = 0 30 + -9x = -10 + 0 30 + -9x = -10 Add '-30' to each side of the equation. 30 + -30 + -9x = -10 + -30 Combine like terms: 30 + -30 = 0 0 + -9x = -10 + -30 -9x = -10 + -30 Combine like terms: -10 + -30 = -40 -9x = -40 Divide each side by '-9'. x = 4.444444444 Simplifying x = 4.444444444
| 6(5x+1)=336 | | 3y-6=2(y+4) | | -27+3y=-9 | | 7-3(x-6)=5x-5 | | (1/4)y-(1/2)=(1/9) | | 4(6x+3)=300 | | 21-3x=4x | | 2x^6-10x^4+10=0 | | 4(6x+3)=3003 | | 4x=6.8 | | 4(x-1)-6=6x-2(4+x) | | 8(2x-6)=5(3x-7) | | f(x)=300x-5x^2+5 | | 3-4(x-3)=3x-12 | | 3(6+6x)=234 | | 8x+5y=1600 | | 30=x+.06x | | f(x)=300x-5x^2-5 | | F(0)=4x^2-9x+8 | | -40-(-53)= | | =300x-5x^2-5 | | 2a^4-5a^3-2a^2+10a-4=0 | | 2(x-7)+x=11 | | 5-x+2x-29=4x-34 | | (6*x)/2-6*5=(6*x)/3 | | 2(10+5x)=50 | | 29-3b+b^2=0 | | 7-6(x-5)=2x-9 | | M-[2-(2-m)]= | | 3x+7=3(x+8) | | a^4+2a^2-63=0 | | 7(1+2x)=161 |